2003
DOI: 10.1117/12.529291
|View full text |Cite
|
Sign up to set email alerts
|

A nonparametric classifier for unsegmented text

Abstract: Symbolic Indirect Correlation (SIC) is a new classification method for unsegmented patterns. SIC requires two levels of comparisons. First, the feature sequences from an unknown query signal and a known multi-pattern reference signal are matched. Then, the order of the matched features is compared with the order of matches between every lexicon symbolstring and the reference string in the lexical domain. The query is classified according to the best matching lexicon string in the second comparison. Accuracy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In [7] and [8], we introduced the SIC classifier with a representation based on bipartite graphs and showed with simulations that at significant noise levels (40% spurious and 40% missed matches) the SIC classifier gives very high accuracy (97% for 50 word lexicons). A significant advantage of SIC over several existing classifiers is that it does not need feature-level samples from every class.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In [7] and [8], we introduced the SIC classifier with a representation based on bipartite graphs and showed with simulations that at significant noise levels (40% spurious and 40% missed matches) the SIC classifier gives very high accuracy (97% for 50 word lexicons). A significant advantage of SIC over several existing classifiers is that it does not need feature-level samples from every class.…”
Section: Resultsmentioning
confidence: 99%
“…For the example of Table 2, the likelihood of assignment be-n-eath-ath is the product of all the elements in Table 2, i.e., 0.15 2 ×0.06×0.85×0.94 8 . The first branch assigned segment S 4 to th instead of ath, so the conditional probability for these was p 1|1 =0.15 instead of p 1|0 =0.06.…”
Section: Correct Rejectionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have formulated both a graph-theoretic 3,5,6 and a probabilistic 5 approach to perform the second-level comparison. Here, we discuss the probabilistic method.…”
Section: Figure 2 the Classifier Can Identify The Partial Word Matchmentioning
confidence: 99%
“…We introduced SIC in [6,7] with a representation based on ordered bipartite graphs and established its advantages through simulations with a significant amount of noise. Later investigations showed that in the presence of excessive noise, the sub-graph isomorphism based approach to the second-level matching requires an unreasonably large reference set [8,9].…”
Section: Arabic Character Recognitionmentioning
confidence: 99%